(untitled) (Transport systems and technologies, 2019)
One of the most important sectors of the national economy of Ukraine is railway transport. The main resource that ensures the efficiency of economic activity in the field of passenger transportation is rolling stock. The advantages of this type of transport are its large ramification and low tariffs. The article analyzes the technical condition of the frame elements of passenger cars. It is shown that the nodes of the frame of passenger cars, namely: spinal beam, shvornevoy beam, end beam, have a fairly large corrosion wear. The obtained graphs of the dependence of the wear of the frame nodes during operation. The most worn-out zones of the nodes of the frame of passenger cars were established. In this situation, the urgent problem is to ensure the operability and maintenance of a reliable technical condition of the existing rolling stock of passenger cars through major overhauls, including modernization and extension of service life. That is, the center of gravity in addressing these issues is currently shifting to the quality of repair activities. It is necessary to look for new approaches to solve the problem of restoring the technical resource of passenger cars.